(untitled) (Third Sector Social Economic Review, 2016)
Individual PensionSystem as the most common application of private pension systems is a saving system tha offers the contributors additional income in old age. As a result of change in demographic structure, the old population is increasing and the benefits provided from social security systems -as PAY-GO systems- are decreasing. Individual Pension System was put in practice in 2001 in Turkey and the savings increased acceleratingly by 2015 with stimulation like tax reduction and government contribution. However, there are some problems to be solved to sustain growth of individual pension system. These are; low-medium risk profile preference of pension company in asset diversification, the short duration of contributors in pension system, and lack of knowledge about the pension system and risk-return profile of pension funds. In this study, concerning the system; some informations are given, some essential problems pointed out and some proposal offered.